2011
DOI: 10.1007/s00405-011-1762-0
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea as a prognostic factor in anaplastic thyroid carcinoma

Abstract: Anaplastic thyroid cancer (ATC) is a rare but aggressive form of thyroid cancer. In this study, we review a single institution's experience with ATC over past 34 years. Through retrospective review, we attempted to identify the prognostic factors affecting the survival at our institution. We reviewed the records of 33 patients diagnosed with ATC by pathology over the last three decades. At our institution, median age at diagnosis was 68 years, the male to female ratio was 1.1:1, mean survival was 10 months and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…Consequently, the significance of surgical resection of the primary tumor remains controversial [6]. In the present study, the extent of resection did not affect survival (χ 2 = 0.005, P = 0.998), which is similar to the findings of other studies [4,8,10,11]. However, most studies have found that curative resection significantly improved the survival of ATC patients [6,1618].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consequently, the significance of surgical resection of the primary tumor remains controversial [6]. In the present study, the extent of resection did not affect survival (χ 2 = 0.005, P = 0.998), which is similar to the findings of other studies [4,8,10,11]. However, most studies have found that curative resection significantly improved the survival of ATC patients [6,1618].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, primary tumor size was not related to the prognosis of ATC patients, although other authors have reported that large tumors correlate with worse outcomes [2,5,8,14,18,36]. As in most reports [10,14,28], our study did not find lymph node metastasis ( P = 0.230) to be a prognostic factor. However, the patients with distant metastasis had worse 1- and 3-year OS rates than did the patients without distant metastasis ( P = 0.032), similar to the findings of other studies [5,8,13,14,18,28,29].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We recommend not to waste precious time, and to secure the airway when there is suspicion of its severe impairment. Tashima et al [8] report that dyspnea at its outbreak is the only significant independent prognostic factor affecting the mortality of ATC. Following Kumar and Joshi's [14] point of view, we assert that a partial or, when it is possible to get a radical surgery, a total thyroidectomy is a possible and life-saving option for palliation of a severe compressive ATC.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients die a few months after diagnosis because of uncontrolled neck mass and metastases, and long-term survivors are rare [1-4]. In the dead patients, dyspnea was the most common cause due to extensive neck mass, and another cause was metastases [5]. A tracheotomy may sometimes be performed to solve airway obstruction, but which also deteriorated the quality of life in the patients.…”
Section: Introductionmentioning
confidence: 99%